Modern architectural theory : a historical survey, 1673-1968 - Mallgrave, Harry Francis, 1947-; ebrary, Inc. (New York : Cambridge University Press, 2005)
Modern Architectural Theory is the first book to provide a comprehensive survey of architectural theory, primarily in Europe and the United States, during three centuries of development. In this synthetic overview, Harry Mallgrave examines architectural discourse within its social and political context. He explores the philosophical and conceptual evolution of its ideas, discusses the relation of theory to the practice of building, and, most importantly, considers the words of the architects themselves, as they contentiously shaped Western architecture. He also examines the compelling currents of French rationalist and British empiricist thought, radical reformation of the theory during the Enlightenment, the intellectual ambitions and historicist debates of the nineteenth century, and the distinctive varieties of modern theory in the twentieth century up to the profound social upheaval of the 1960s. Modern Architectural Theory challenges many assumptions about architectural modernism and uncovers many new dimensions of the debates about modernism.
1, Prelude -- 2, The Enlightenment and Neoclassical Theory -- 3, British Theory in the Eighteenth Century -- 4, Neoclassicism and Historicism -- 5, The Rise of German Theory --6, Competing Directions at Midcentury -- 7, Historicism in the United States -- 8, The Arts and Crafts Movements -- 9, Excursus on a Few of the Conceptual Foundations of Twentieth-Century German Modernism -- 10, Modernism 1889-1914 -- 11, European Modernism 1917-1933 -- 12, American Modernism 1917-1934 -- 13, Depression, War, and Aftermath 1934-1958 -- 14, Challenges to Modernism in Europe 1959-1967 -- 15, Challenges to Modernism in America
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: 17.-20. století; 1673-1968; dějiny architektury -- 17.-20. století; moderní architektura -- 17.-20. století; teorie architektury -- 17.-20. století; architektura -- filozofické aspekty; history of architecture -- 17th-20th centuries; modern architecture -- 17th-20th centuries; theory of architecture -- 17th-20th centuries; architecture -- philosophical aspects; přehledy; e-knihy online; surveys; e-books online